2018
DOI: 10.1103/physrevb.97.214102
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced polarization rotation and phase transitions in 0.70Pb(Mg1/3Nb2/

Abstract: Changes to the crystal structure of 0.70Pb(Mg 1/3 Nb 2/3)O 3-0.30PbTiO 3 (PMN-0.30PT) piezoceramic under application of electric fields at the long-range and local scale are revealed by in situ high-energy X-ray diffraction (XRD) and pair distribution function (PDF) analyses, respectively. The crystal structure of unpoled samples is identified as monoclinic Cm at both the long-range and local scale. In situ XRD results suggest that field-induced polarization rotation and phase transitions occur at specific fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 59 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…Other evidence suggests that for PIN-PMN-PT 8 and PMN-PT 32–34 crystals with compositions close to the MPB, poling changes the crystallographic symmetry. X-ray diffraction shows that field cooling a crystal that is initially rhombohedral at room temperature, produces a monoclinic symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence suggests that for PIN-PMN-PT 8 and PMN-PT 32–34 crystals with compositions close to the MPB, poling changes the crystallographic symmetry. X-ray diffraction shows that field cooling a crystal that is initially rhombohedral at room temperature, produces a monoclinic symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Polarization rotation, which was identified as the main mechanism responsible for the property enhancement in relaxor ferroelectrics, [25] was directly evidenced during field application by in situ pair distribution function analysis on PMN-PT. [26] While the described models explain the effects of PNR dynamics or the presence of high density low-angle domain walls on the lattice response under external fields in terms of the polarization rotation mechanism, it is not clear how this nanoscale structure in relaxor-based materials affects the motion of domain walls and thus the macroscopic piezoelectric response, and whether it can relate to high properties of compositions at different parts of the phase diagram. This is particularly important for the high performance polycrystalline relaxor ferroelectrics where, unlike in domain-engineered single crystals, the nonlinear and hysteretic domain-wall contributions may dominate the total piezoelectric response.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] Polarization rotation, which was identified as the main mechanism responsible for the property enhancement in relaxor ferroelectrics, [ 25 ] was directly evidenced during field application by in situ pair distribution function analysis on PMN–PT. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric constants of PMN-PT with x = 0.30 (PMN-30PT) and PZN-PT with x = 0.08 (PZN-8PT) near their MPBs exceed 2 × 10 3 pC/N [7,8]. It has been suggested that electric field-induced phase transitions involving polarization rotation and electric field responses of polar nano regions (PNRs) aiding the polarization rotation explain the enormous piezoelectric capabilities around MPB [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Monoclinic and orthorhombic phases exist in a narrow composition region near MPB and are easily induced by applying an electric field [8,10,11,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that electric field-induced phase transitions involving polarization rotation and electric field responses of polar nano regions (PNRs) aiding the polarization rotation explain the enormous piezoelectric capabilities around MPB [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Monoclinic and orthorhombic phases exist in a narrow composition region near MPB and are easily induced by applying an electric field [8,10,11,14,17,18]. PNRs first occur below the Burns temperature in the high-temperature paraelectric cubic phase, expanding with cooling and coexisting with regular ferroelectric domains in low-temperature ferroelectric phases [21].…”
Section: Introductionmentioning
confidence: 99%